Dampak Pemasaran Melalui Media Sosial terhadap Keputusan Pembelian Konsumen di Industri Fashion terhadap Kepercayaan Merek ZARA - Meliasari, Maya; Suryasuciramdhan, Arfian; Lestari, Vina; Badarzaman, Bintang Ramadhan; Muadz, Muadz (Buana Komunikasi (Jurnal Penelitian dan Studi Ilmu Komunikasi), 2025)
Increasingly tight business competition requires companies to not only offer quality products, but also build customer satisfaction and strong trust in brand image. Customer satisfaction is the main indicator in assessing the success of service, while trust in the brand reflects consumer perception and belief in the consistency and integrity of the company. This study refers to the theory of brand image, customer satisfaction, and customer trust as a conceptual framework. The methodology used is a qualitative approach by applying meta-analysis studies obtained from several studies that have been conducted previously. The results of the study indicate that customer satisfaction and comfort obtained from the service have a significant effect on the positive image of the company. This study confirms that consistent improvement in service quality and management of positive brand image can increase customer satisfaction and build sustainable trust, which ultimately strengthens consumer loyalty.